OPTIMALISASI SOSIALISASI KEAGAMAAN BERBASIS PENDIDIKAN ISLAM DALAM MENINGKATKAN KARAKTER SOSIAL MASYARAKAT DESA SUKANDEBI - Muhammad Getsy Terrano; Oktrigana Wirian (Saweu: Jurnal Pengabdian Kepada Masyarakat, 2025)
This study examines the optimization of Islamic education-based religious socialization in improving the social character of the Sukandebi Village community. The focus of this research is how Islamic education, through formal and non-formal activities, can instill moral and social values such as tolerance, solidarity, responsibility, and concern for others. The results show that the systematic and sustainable implementation of religious socialization can shape a religious society that also possesses a strong, harmonious, and competitive social character in facing the dynamics of modernization. These findings emphasize the important role of Islamic education as a strategic tool in developing the social character of the village community.